Eucomic acid methanol monosolvate - Li, Guo-Qiang (International Union of Crystallography, 2011)
In the crystal structure of the title compound [systematic name: 2-hydroxy-2-(4-hydroxybenzyl)butanedioic acid methanol monosolvate], C(11)H(12)O(6)·CH(3)OH, the dihedral angles between the planes of the carboxyl groups and the benzene ring are 51.23 (9) and 87.97 (9)°. Intermolecular O—H⋯O hydrogen-bonding interactions involving the hydroxy and carboxylic acid groups and the methanol solvent molecule give a three-dimensional structure.